Application of the international classification of functioning in the rehabilitation examination of children of the palliative non-oncology group - Grygus, Igor; Nahorna , Olga (Journal of Education, Health and Sport, 2021)
Annotation. Rehabilitation of children who need palliative non-oncology care is a complex and multi-vector task. WHO defines palliative pediatric care as a complex of active care for the physical and mental state of the child, its cognitive abilities, as well as support for the patient's family. To provide comprehensive palliative care that is child- and family-centered, it is possible to use the International Classification of Functioning to examine and build a rehabilitation system. The purpose of the study: to analyze the application of the international classification of functioning in the process of rehabilitation examination of children who need palliative care. Research methods: empirical methods (comparison, description, measurement), theoretical method (axiomatic), general logical methods (analysis, synthesis, generalization). The study was conducted on the basis of the Rivne Educational and Rehabilitation Center «Special Child» 47 (100%) children took part in the study. Research results. The International Classification of Functioning-Children, Adolescents (ICF-DP) was used to define a set of tools for rehabilitation assessment of pediatric patients. Taking into account the psychometric criteria of the assessment scales, the following were selected for the examination of the Structure and function of the body component: s 710 – brain structure – disease history and systematized diagnoses according to ICD-10; Pain sensation (b 280) – 5-point scale of verbal assessments, visual-analog scale of pain intensity (10 points), FLACC scale; Joint mobility functions (b 710) – goniometry; Muscle tone functions (b 735) – Modified Ashforth spasticity scale; to analyze the problem Sleep functions (b 134) allowed a survey of parents; observing the control of voluntary motor functions (b 760) contributed to the study of the state of the problem. Examination of the domains of the Activity and Participation component was provided by the PEDI Pediatric Disability Questionnaire, parent questionnaire, observation of pediatric patients: communication (d 310-340), Schooling (d 820), recreation, leisure (d 920) – PEDI Pediatric Disability Questionnaire (assessment social functions); d 550 nutrition – PEDI pediatric disability questionnaire (self-care); moving from place to place (d 460) – Classification of the system of general motor functions GMFCS; use of precise movements of the hand and hand (d 440) – MACS fine motor development level (levels), «Box and cubes» test; maintaining body position (d 415) – observation. Through survey and observation, the Environmental Factors component examined the presence of facilitating or barrier factors. In the aspect of personal factors, the patient's age, gender, and motivation for physical therapy classes were analyzed. Structure and function disorders were found in 43% of the overall assessment, activity and participation limitations covered 39%, and environmental factors – 18%. A review of limitations and impairments confirms that the greatest problem in pediatric patients requiring palliative care is in the Activity and Participation component (182 points). Therefore, the use of the International Classification of Functioning – Children, Adolescents contributes to the selection of tools for assessing the functioning of children in need of palliative care, and ensures the control of the effectiveness of rehabilitation. Conclusions. Evaluation of pediatric patients who belong to the non-oncology palliative group is a complex, multifaceted task, since complex disorders and pathological conditions prompt the search for evaluation resources that would allow monitoring the effectiveness of the rehabilitation process. The International Classification of Functioning, which is represented by the Basic Set «Childhood Cerebral Palsy» provides those domains that fully reveal the needs of a child with a disability in all areas of life – Structures and functions of the body, Activity and Participation, Environmental factors. The international classification of functioning must be used to assess the pathological condition of a pediatric patient, since it is the multifaceted examination that will ensure the formation of a multifaceted rehabilitation program.